Billionaires in world politics: how can they be approached as potential legitimate private authorities?. Issue 2 (4th May 2022) - Latorre, Indira
ABSTRACT: Peter Hägel's Billionaires in World Politics undoubtedly fills a gap in the literature of international relations and global governance. My comment seeks to highlight that Hägel's (2020. Billionaires in World Politics . 1st ed. Oxford Scholarship Online. Oxford: Oxford University Press) work allows us to advance our understanding of how these private actors can be understood as legitimate authorities and how they can contribute to the legitimacy of the international order. I divide my commentary into three points: the first concerns the approach to billionaires from their individual agency (the individual approach), the second relates to the separation between the state and the global levels (the division approach), and the third presents questions on political legitimacy that arise from his case studies (the legitimacy question).